RADIOSENSITIVITAS BAWANG MERAH (Allium ascalonicum L.) LOKAL SULAWESI TENGGARA TERHADAP IRADIASI GAMMA (THE RADIOSENSITIVITY OF SOUTHEAST SULAWESI LOCAL ONION TO GAMMA IRRADIATION) - ni wayan sri suliartini *1); Asniah *2); Wa Ode Nuraida*2) (CROP AGRO, Scientific Journal of Agronomy, 2019)
ABSTRACT Onion is one of the vegetable commodities that have significance for the community, both from economic value and nutritional content. In the last decade the demand for onion for consumption and for domestic seeds has increased, so that Indonesia must import to meet those needs. The production and quality of onion shall always be enhanced through intensification and extensification. Induction of mutation as one of the methods of plant breeding to obtain genetic diversity is expected to meet the expectations in increased onion production.The purpose of this research was to find out radiosensitivity and the effect of various dosages of gamma on onion (Allium ascalonicum L.) growing. The research materials were two Southeast Sulawesi onion landraces namely Landrace Tomia and Landrace Buton. Gamma irradiation was conducted at the Center for Application Technology Isotope and Radiation, National Nuclear Agency, Jakarta. Onion bulbs were irradiated by 60Co gamma at dosages of 2, 4,6, and 8 Gy. It was found that the landrace Buton was more sensitive than the landrace Tomia. Gamma irradiation increases plant height, number of leaves mutant landace Tomida except dose 8 Gy and increases number of tillers at all doses of gamma irradiation. Gamma irradiation increases plant height, number of leaves and number of tillers at all treatment doses. All of the observed variables underwent increases after the gamma irradiation except for a dose of 8 Gy on Landrace Tomia. Based on the observed data, the results of this research showed: (1) the Buton was more sensitive than the Tomia; (2) the dosages of irradiation affect the sensitivity of the plant. Keywords: Onion, gamma rays, radiosensitivity, Southeast Sulawesi ABSTRAK Bawang merah merupakan salah satu komoditas sayuran yang mempunyai arti penting bagi masyarakat, baik dilihat dari nilai ekonomis maupun kandungan gizi. Dalam dekade terakhir ini permintaan akan bawang merah untuk konsumsi dan untuk bibit dalam negeri mengalami peningkatan, sehingga Indonesia harus mengimpor untuk memenuhi kebutuhan tersebut. Produksi dan mutu hasil bawang merah harus senantiasa ditingkatkan melalui intensifikasi dan ekstensifikasi. Induksi mutasi sebagai salah satu metode pemuliaan tanaman untuk memperoleh keragaman genetik diharapkan dapat memenuhi harapan dalam peningkatan produksi bawang merah. Penelitian bertujuan untuk mengetahui radiosensitivitas dan pengaruh iradiasi gamma terhadap pertumbuhan dua landrace bawang merah Sulawesi Tenggara. Bahan penelitian yaitu dua landrace bawang merah Sulawesi Tenggara yaitu Landrace Tomia dan Landrace Buton. Iradiasi gamma dilakukan dengan 60Co di Pusat Aplikasi Isotop dan Radioaktif Badan Tenaga Atom Nasional (PATIR BATAN), Pasar Jumat Jakarta. Bawang merah diradiasi pada dosis 2,4,6 dan 8 Gy. Hasil penelitian menunjukkan bahwa Landrace Buton lebih sensitif terhadap iradiasi gamma dibandingkan dengan Landrace Tomia. Kata kunci: bawang merah,sinar gamma, radiosensitivitas, Sulawesi Tenggara